Vignetten von Konstantinopel in den Mittelalterlichen und Frühneuzeitlichen Karten. Die Entwicklung eines Graphischen Topos der Stadt (Winiety Konstantynopola na mapach średniowiecznych i wczesno-nowożytnych. Ewolucja graficznego toposu miasta) - Kochanek, Piotr (Vox Patrum, 2018)
The article is based on the analysis of 45 vignettes of Constantinople, which are on the maps created in the years 775-1679. This study has been divided into two parts. The first part contains „metrics” of the analyzed maps (1-41B), arranged in chronological order, and table (I), in which reproductions of the above-mentioned 45 vignettes of the Greek Metropolis were placed. The layout of this table corresponds with the layout of the „metrics” of the maps. The second part of the article consists of seven tables (II-VIII), in which the material from table I was used. These tabular statements represent different variants of the graphic topos of Constantinople, accompanied by analytical comments. And so table II groups vignettes presenting Constantinople as a fortified town. Table III collects, in turn, vignettes that depict the City as a donjon or burg. Table IV contains the vignettes on which Constantinople has a scheme of the defensive city gate. Table V, in turn, shows the evolution of the graphic topos of the City, in which the elements of sacral architecture dominate, emphasizing the importance of Constantinople as one of the capitals of Pentarchy. Table VI, on the other hand, collects mini view (vedute) of the Greek Metropolis. In turn, Table VII shows the city’s fortifications from the profile, and in front of them locates the Genoese district of Pera, lying on the other side of the Golden Horn. Finally, the last table (VIII) presents the vignettes whose graphic content does not fit into any of the above mentioned topoi. As a consequence, the article distinguishes six graphical topoi of Constantinople (Table II-VII), which can be found on its cartographic vignettes between 775 and 1679.